Maximising umami taste in meat using natural ingredients: effects on chemistry, sensory perception and hedonic liking in young and old consumers. (7th June 2013) - Dermiki, Maria; Mounayar, Rana; Suwankanit, Chutipapha; Scott, Jennifer; Kennedy, Orla B; Mottram, Donald S; Gosney, Margot A; Blumenthal, Heston; Methven, Lisa
Abstract: BACKGROUND: Umami taste in foods is elicited predominantly by the presence of glutamic acid and 5′‐ribonucleotides, which act synergistically. This study aimed to use natural ingredients to maximise umami taste of a meat formulation and determine effects on liking of older consumers. Cooked meat products with added natural ingredients (yeast extract, mycoscent, shiitake extract, tomato puree, soy sauce and soybean paste) or monosodium glutamate (MSG) were prepared and compared with a control sample analytically (umami compounds), sensorially (sensory profile) and hedonically (liking by younger and older volunteers). Taste detection thresholds of sodium chloride and MSG of volunteers were collected . RESULTS: Four of the seven cooked meat products developed had a significantly higher content of umami‐contributing compounds compared with the control. All products, except those containing MSG or tomato puree, were scored (by trained sensory panel) perceptually significantly higher in umami and/or salty taste compared with the control. Consumer tests showed a correlation of liking by the older cohort with perceived saltiness ( ρ = 0.76) . CONCLUSION: The addition of natural umami‐containing ingredients during the cooking of meat can provide enhanced umami and salty taste characteristics. This can lead to increased liking by some consumers, particularly those with raised taste detection thresholds. © 2013 Society of Chemical Industry